Pure arterial malformation on the azygous anterior cerebral artery in a patient with unilateral moyamoya phenomenon and contralateral internal carotid artery occlusion - Jinlu Yu, PhD (Radiology Case Reports)
To date, there have been no reports of a pure arterial malformation (PAM) on the azygous anterior cerebral artery (ACA) with a unilateral moyamoya phenomenon and contralateral internal carotid artery (ICA) occlusion. Herein, we report such a case. A 55-year-old male experienced three hemorrhages. In the first hemorrhage, the coexistence of the PAM on the azygous ACA and the unilateral moyamoya phenomenon of the left middle cerebral artery was confirmed. The hemorrhage was caused by the rupture of a coiled aneurysm inside the PAM. The patient subsequently experienced repeated hemorrhages. At the time of the last hemorrhage, the patient was drowsy and could not obey orders. He also presented with left hemiparesis. The Hunt–Hess scale score was Grade III. Right intracranial ICA occlusion on the opposite side of the moyamoya phenomenon was observed via angiography. A ruptured aneurysm on the branch of the ACA, causing the third hemorrhage, was confirmed and embolized to prevent rebleeding. Then, burr hole drainage was performed to resolve the intracerebral hemorrhage. Postoperatively, the patient had no new neurologic deficits. Ten days later, his left hemiparesis was relieved. One month later, he could walk. This is the first case report of the coexistence of a PAM on the azygous ACA with the unilateral middle cerebral artery moyamoya phenomenon and contralateral ICA occlusion. When these abnormalities coexist, the ACA will experience more hemodynamic stress. Flow-related aneurysms can occur inside the PAM or on the azygous ACA branches. Endovascular treatment can be a therapeutic option.